Peningkatan Literasi Digital dan Manajemen Keuangan untuk UMKM di Desa Trimulyo - Swissia, Pebrina; h, Halimah; Marshella, Ochi (Jurnal Pengabdian Masyarakat Tapis Berseri (JPMTB), 2025)
MSMEs have a strategic role in local economic growth, but still face various challenges, especially in utilizing digital technology for marketing and effective financial management. Low digital literacy and lack of understanding of good financial records are the main obstacles for MSMEs in developing their businesses. The methods applied in this program include several stages, namely (1) Survey to identify the conditions and needs of MSMEs, (2) Socialization and Education to introduce the importance of digital literacy and financial management for business sustainability, (3) Digital Literacy and Financial Management Training provided directly to MSMEs, (4) Mentoring sessions to help MSMEs apply the knowledge they have gained. The results of the activities showed an increase in participants' understanding in using digital technology to support their product marketing. MSMEs that previously only relied on conventional methods began to utilize social media such as Facebook, Instagram, and WhatsApp Business to reach more customers. In addition, in terms of finance, participants began to implement more systematic recording of business transactions using simple applications such as Excel and mobile-based financial applications. Awareness of the importance of separating personal and business finances has also increased, helping business actors manage finances more effectively.